Monitoring and Controlling of pH Levels and Plant Nutrition Supplied by Standalone Photovoltaic in a Greenhouse Hydroponic System using Arduino Uno - Kurniawan, Lutfi Athanuzul; Amirullah, Amirullah (Faculty of Engineering, Universitas Tanjungpura, 2021)
This paper aims to implement the prototype model to monitor and control the pH levels and nutrition plant (electrical conductivity-EC) supplied by a standalone photovoltaic (PV) module-connected battery (Lithium-Ion) on the greenhouse hydroponic systems. The pH and EC sensors are connected to the Arduino Uno circuit as a relay control to drive four pumps, i.e. the water flow pump, EC pump, pH up pump, and pH down pump. The greenhouse function to control pests and the impact of environmental non-uniformity caused by variation of wind speed, temperature, or sunlight so that hydroponic plants can grow in an appropriate environment. The Arduino Uno circuit with a 20 Ã— 4 liquid crystal display (LCD) order four relays to monitor and control the four pumps of the greenhouse hydroponic system based on the coding which has been programmed previously. The prototype model is able to monitor and control the pH of hydroponic plant water at the level between 6-7 using a pH-up and pH-down sensor. This model is also able to monitor and control nutrition plant water over 1 mS/cm using an EC sensor. Finally, the proposed prototype is able to monitor and control EC and pH level to regulate plant growth in the greenhouse hydroponic system normally and in real-time.